Man-environment relationship - Bhasin, M.K.; Bhasin, Veena (Delhi: Kamila Raj Enterprises, 2000)
This volume, edited in honour of Professor Roche, comprises articles written by scholars from all over the world. It reflects the idea that today ecological studies are not only multi-disciplinary but also multinational. The volume shows that ecology is the meeting point of different systems, biological, socio-cultural, psychological, and this approach can be need for understanding man-environment relationship and also, for resolving ecological crises. The volume has twenty six papers that are classified into the following five units. I. An Overview, II. Environment in the Perspective of Past, III. Ecological Adaptation, IV. Ecological Biology, V. Ecology and Culture.
A tribute to Dr. Alexader Francis Roche -- I. An overview -- II. Environment in the perspective of past -- III. Ecological adaptation -- IV. Ecological biology -- V. Ecology and culture
Keywords: Human Ecology